Kajian Kapasitas Sungai Sengkarang Kabupaten Pekalongan Dengan Menggunakan HEC-RAS - Johanes Among Timur; Abraham Daksa; Budi Santosa (Universitas Katolik Soegijapranata Semarang, 2019)
Flooding was natural disasters the minimize the impact or can be avoided when you know a source of the problem. The increase in discharge flood most affected by the existence of the to watershed ( DAS ), and the form of profile river that could not be accommodate flooding luminance stretch out. The purpose of this research is to evaluate capacity river Sengkarang in order to accommodate flooding luminance stretch out, and give the alternative solution flood. The necessary data in the form of rainfall daily from year 2001 - 2016 in five station rain, namely station Karang Gondang, PS.Kletak station, Karangsari station, Pekalongan station, and Kutosari station. Daily rainfall data is then processed into hourly rain data using Mononobe method. Then from the parameters that have been specified in the insert into HEC-HMS software. The result of HEC-HMS this is discharge flood simulations with the period repeated 2 annual of 322.8 m3 / s, the period repeated 5 annual of 582.6 m3 / s, the period repeated of 10 years of 765.1 m3 / s, the period repeated 25 annual of 1034.3 m3 / s, the period repeated 50 annual of 1148.9 m3 / s. after obtained discharge simulations with the period repeated certain then afterward did the simulation profile river sengkarang by using HEC-RAS software. This permodelan it can be found in which a part is happened flood. Therefore done solution altermatif of normalization river.